On the classical character of Sheffer-Meixner 2-orthogonal polynomials type - Ali Krelifa (Université de M'sila, 2020)
In this paper we study the classical character of 2-OPS whose generating function satisfies a first order differential equation. Our results give some information about the classical character of the 2-Sheffer-Meixner type polynomials